Effect of teaching English with the eclectic approach on Saudi Arabian students’ communicative skills - HAKIM, B.M. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT This study aims to investigate the effect of an eclectic teaching method on the communicative skills of listening, speaking, reading and writing on the foundation year students, level 104, at the English Language Institute of King Abdulaziz University in Jeddah, Saudi Arabia. The predicted objective of the present study is to observe, and determine, the effect of the eclectic approach on these four skills. The study revealed that the experimental group, taught under the eclectic approach, performed significantly better than the control group, taught according to the scheduled program. RESUMEN Este estudio tiene como objetivo investigar el efecto de un método de enseñanza ecléctico en las habilidades comunicativas de escuchar, hablar, leer y escribir en los estudiantes de primer año, nivel 104, en el Instituto de Idioma Inglés de la Universidad King Abdulaziz en Jeddah, Arabia Saudita. El objetivo previsto del presente estudio es observar y determinar el efecto del enfoque ecléctico en estas cuatro habilidades. El estudio reveló que el grupo experimental enseñado bajo el enfoque ecléctico, se desempeñó significativamente mejor que el grupo control, enseñado de acuerdo al programa.